Electronic cigarettes: The nicotyrine hypothesis. Issue 3 (September 2015) - Abramovitz, Aaron; McQueen, Amy; Martinez, Raul E.; Williams, Brent J.; Sumner, Walton
Abstract There are conflicting reports about the efficacy of electronic cigarettes (e-cigs) as nicotine delivery devices and smoking cessation products. In addition, smokers' responses to some nicotine dependence questions often change as they transition to exclusive e-cig use. Nicotyrine may explain these observations. Nicotyrine forms by the gradual oxidation of nicotine in e-liquids exposed to air. E-cigs aerosolize nicotyrine along with nicotine. Nicotyrine inhibits the cytochrome P450 2A family of enzymes (CYP2A) in airways and liver. These enzymes metabolize nicotine to cotinine, and then cotinine to trans 3-hydroxycotinine. In humans, nicotine is metabolized primarily by hepatic CYP2A6. We propose that e-cig users (vapers) achieve measurable serum nicotine levels when they inhale nicotine and nicotyrine together, because nicotyrine reversibly inhibits nicotine metabolism by CYP2A13 in airways. Consuming nicotyrine by any route should irreversibly inhibit hepatic CYP2A6. When CYP2A6 is substantially inhibited, nicotine clearance is delayed and nicotine withdrawal symptoms are attenuated. Small, relatively infrequent nicotine doses can then sustain satisfying nicotine levels. This theory has numerous implications for e-cig research and tobacco control. Behavioral and pharmacokinetic e-cig studies should be interpreted with attention to likely levels of nicotyrine delivery: e-cig studies may need to routinely measure nicotyrine exposure, assess CYP2A6 activity, confirm nicotine delivery, or deliberately compare unoxidized and oxidized e-liquids. The risks of nicotyrine exposure include impaired clearance of all CYP2A substrates and any effects of the metabolic products of nicotyrine. CYP2A inhibitors like nicotyrine may be useful for future smoking cessation therapy.